Membranous structures transfer cell surface proteins across NK cell immune synapses. - Williams, G; Collinson, L; Brzostek, J; Eissmann, P; Almeida, C; McCann, F; Burshtyn, D; Davis, D (2007)
Intercellular transfer of cell surface proteins is widespread and facilitates several recently discovered means for immune cell communication. Here, we examined the molecular mechanism for intercellular exchange of the natural killer (NK) cell receptor KIR2DL1 and HLA-C, prototypical proteins that swap between NK cells and target cells. Transfer was contact dependent and enhanced for cells expressing cognate receptor/ligand pairs but did not depend on KIR2DL1 signaling. To a lesser extent, proteins transferred independent from specific recognition. Intracellular domains of transferred proteins were not exposed to the extracellular environment and transferred proteins were removed by brief exposure to low pH. By fluorescence microscopy, transferred proteins localized to discrete regions on the recipient cell surface. Higher resolution scanning electron micrographs revealed that transferred proteins were located within specific membranous structures. Transmission electron microscopy of the immune synapse revealed that membrane protrusions from one cell interacted with the apposing cell surface within the synaptic cleft. These data, coupled with previous observations, lead us to propose that intercellular protein transfer is mediated by membrane protrusions within and surrounding the immunological synapse.